2018
DOI: 10.1111/sms.13198
|View full text |Cite
|
Sign up to set email alerts
|

When does the influence of maturation on anthropometric and physical fitness characteristics increase and subside?

Abstract: The relationships between maturation and anthropometric and physical performance characteristics are dynamic and often asynchronous; confounding the capability to accurately evaluate performance during adolescence. This study aimed to (i) examine the influence of chronological age (CA) and somatic maturation (YPHV) upon anthropometric and physical performance parameters, and (ii) identify the transition/change time points in these relationships using segmental regression. N = 969 soccer players (8-18 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 39 publications
2
71
0
Order By: Relevance
“…During the growth process, the relationship between anthropometric variables and physical performance have a higher level of complexity [13] and numerous differences can occur in the morphological growth and physiological development of players. Therefore, in preadolescent players, differences in growth rate and development can be a confounding factor affecting performance and success [14]. It is well known that adolescent growth and biological maturation strongly influence physical performance [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…During the growth process, the relationship between anthropometric variables and physical performance have a higher level of complexity [13] and numerous differences can occur in the morphological growth and physiological development of players. Therefore, in preadolescent players, differences in growth rate and development can be a confounding factor affecting performance and success [14]. It is well known that adolescent growth and biological maturation strongly influence physical performance [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The question we want to explore is whether children belonging to the same category of competition have different maturations, which leads to an unbalanced confrontation, since athletes with higher maturation levels have greater physical skills (Anderson & Ward, 2002;Backous et al, 1990;Pieter, 2012;Towlson et al, 2018), which in turn increases the chance of winning (Gabbett, 2015). Analyzing these evaluations by the category of competition, we found that there were several categories with maturational advanced athletes, showing that competitive equity may be at stake.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the differences in maturation among children, chronological age remains the main criterion for equalizing the competition levels, but with limited efficiency (Malina, 2000). These differences in maturation among athletes or differences between chronological and biological age have been studied since the beginning of the 20 th century (e.g., Crampton, 1908), and have pointed out that maturational status had significant influences in physical fitness (Anderson & Ward, 2002;Backous, Farrow, & Friedl, 1990;Towlson, Cobley, Parkin, & Lovell, 2018), performance (Pieter, 2012), and body dimensions (Backous et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for the absence of positive results in the performance measures may be that the population was included during a period of growth and maturation, and thus the players may have had reduced ability to perform optimally. Three different factors may have contributed: 1) difficulties in focusing on the task and performing with maximum effort during training and testing, as identified by Soligard et al 158 , 2) temporary regression of motor control during a growth spurt 140 and 3) the training stimuli needed to elicit positive training effects and the potential for improvement may vary during adolescence since development during puberty is asynchronous, with different abilities developing at different ages 170 . Both studies included players with a mean age of 14.…”
Section: Programme Characteristics Influencing Adoption and Use Of Knmentioning
confidence: 99%